Solar Dynamics and Magnetism from the Interior to the Atmosphere - Mansour, Nagi N.; Kosovichev, Alexander G.; Komm, Rudolf; Longcope, Dana.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
NASA's Solar Dynamics Observatory (SDO) mission has provided a large amount of new data on solar dynamics and magnetic activities during the rising phase of the current and highly unusual solar cycle. These data are complemented by the continuing SOHO mission, and by ground-based observatories that include the GONG helioseismology network and the New Solar Telescope. Also, the observations are supported by realistic numerical simulations on supercomputers. This unprecedented amount of data provides a unique opportunity for multi-instrument investigations that address fundamental problems of the origin of solar magnetic activity at various spatial and temporal scales. This book demonstrates that the synergy of high-resolution multi-wavelength observations and simulations is a key to uncovering the long-standing puzzles of solar magnetism and dynamics. This volume is aimed at researchers and graduate students active in solar physics and space science. Previously published in Solar Physics journal, Vol. 287/1-2, 2013.
Local and Global Helioseismology -- Sources of Solar Shape and Irradiance Variations -- Large-Scale Dynamics, Magnetism and Dynamo -- Emerging Magnetic Flux and Subsurface Dynamics -- Formation, Structure and Evolution of Sunspots and Active Regions -- Magnetic Topology and Dynamics of the Solar Atmosphere.
Keywords: Physics; Astrophysics; Physics; Extraterrestrial Physics, Space Sciences